Are the current account imbalances on a sustainable path? - Seema Narayan; Sivagowry Sriananthakumar (Journal of Risk and Financial Management, 2020)
This paper examines the current accounts of 16 developed and developing countries over the period 1970 to 2018. We test whether these nations satisfy their intertemporal solvency condition for external imbalances. The solvency condition in the strong form entails: (1) a cointegration, or a long run equilibrium, relationship between exports and imports of goods and services; and (2) an increase in imports leading to a proportional increase in exports. Our findings imply that the external imbalances are a cause of vulnerability for several nations. Bangladesh satisfies the abovementioned solvency condition-in other words, its current account is sustainable in the strong form. Australia, Ecuador, Honduras, Mexico, New Zealand, and Venezuela show weak forms of sustainability. For these six nations, the presence of a cointegration relationship between exports and imports coincides with less than proportional increases in exports with increases in imports. The current accounts of Chile and Paraguay are unsustainable-while their exports and imports are cointegrated, a growth in imports leads to a more than proportional increase in exports. For a few nations that failed the full sample (1970-2018) cointegration test, we developed sub-samples by anchoring the start date at 1970 and increasing the sample by every five years from 1999 to 2014. From the sub-samples, we find evidence of intermittent, but weak, cases of sustainability for Peru and South Africa. We show that Panama's current account became unsustainable after 2009. China's current account satisfied the strong form of sustainability between all sub-samples until 2014 and became unsustainable in the most recent four years (2015-2018). France, the Philippines, and the United States unequivocally failed the intertemporal solvency test in the full sample and sub-sample analyses. The cointegration tests allow for structural breaks in exports and imports. We find these breaks have strong economic significance. For instance, we find that for most countries the structural break in exports coincides with their worst economic recession.
Keywords: F14; 330; current account sustainability; developed nations; developing nations; intertemporal solvency theory